Synthesis and magnetic properties of La3+-Co2+ substituted strontium ferrite particles using modified spray pyrolysis–calcination method. Issue 4 (March 2017) - Hwang, Tae-Yeon; Lee, Jimin; Lim, Hyo-Ryoung; Jeong, Seung-Jae; An, Guk-Hwan; Kim, Jongryoul; Choa, Yong-Ho
Abstract: The purpose of the research was to improve the intrinsic magnetic properties of strontium ferrite by substituting lanthanum and cobalt for strontium and iron. The salt-assisted ultrasonic spray pyrolysis (SA-USP) following calcination process were used to from La-Co substituted strontium ferrite particles (La x Sr1- x Fe12 -y Co y O19 ), and their compositional dependent magnetic properties systemically investigated. All the samples were calcined at 1050 °C for 1 h in an air atmosphere to yield single-phased hexagonal particles several hundred nanometers to microns in size. A saturation magnetization of 70.76 emu/g and a coercivity 7265 Oe were obtained at a composition of La0.25 Sr0.75 Fe11.75 Co0.25 O19 . The amount of Co was reduced to obtain an optimized saturation magnetization of 71.40 emu/g and a coercivity of 7572 Oe at a composition of La0.25 Sr0.75 Fe11.8 Co0.2 O19 .